1953
DOI: 10.1177/004051755302301106
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Draw Ratio and Temperature on Electrical Conduction in Nylon Filaments

Abstract: In a study of electrical conduction in nylon as a function of draw ratio and temperature, it was found that the conductance depends upon washing history. Accordingly, a standard washing procedure was devised to allow reproducible and comparable measurements to be made. The conductivity at 30°C thus measured was shown to decrease with increasing draw ratio to an extent greater than can be accounted for by the decreased moisture regain produced by drawing. Upon decreasing the temperature from 45°C to 15&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1955
1955
1977
1977

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Ilersh and Montgomery 1151 I studied conduction in single fibers and were il agreement with the results obtained by Marsh and Earp, Sharman, l lersh, and Montgomery (22) found that the resistance of nylon fil>ers showed a large time delay for the attainment of an equilibrium conduction following the estal~lishrnent of equilibrium moisture content. They considered that the slow resistance change could 1)(' due to a reclistrilnltion of the water within the filter.…”
Section: Introductionsupporting
confidence: 72%
“…Ilersh and Montgomery 1151 I studied conduction in single fibers and were il agreement with the results obtained by Marsh and Earp, Sharman, l lersh, and Montgomery (22) found that the resistance of nylon fil>ers showed a large time delay for the attainment of an equilibrium conduction following the estal~lishrnent of equilibrium moisture content. They considered that the slow resistance change could 1)(' due to a reclistrilnltion of the water within the filter.…”
Section: Introductionsupporting
confidence: 72%
“…A brief outline of the preliminary results of this study was given earlier [18]. In the interpretation of the results it is necessary to know something about the resistance of the insulators, and in earlier experiments [16,33] this topic was studied. The present paper is concerned with the effect of mechanical parameters and ambient conditions on the charge generated when filaments of various materials are rubbed together.…”
Section: Introductionmentioning
confidence: 99%